Refined mapping of autoimmune disease associated genetic variants with gene expression suggests an important role for non-coding RNAs. (April 2016) - ,; ,; Heijmans, Bastiaan T.; 't Hoen, Peter A.C.; van Meurs, Joyce; Isaacs, Aaron; Jansen, Rick; Franke, Lude; Boomsma, Dorret I.; Pool, René; van Dongen, Jenny; Hottenga, Jouke J.; et al.
Abstract: Genome-wide association and fine-mapping studies in 14 autoimmune diseases (AID) have implicated more than 250 loci in one or more of these diseases. As more than 90% of AID-associated SNPs are intergenic or intronic, pinpointing the causal genes is challenging. We performed a systematic analysis to link 460 SNPs that are associated with 14 AID to causal genes using transcriptomic data from 629 blood samples. We were able to link 71 (39%) of the AID-SNPs to two or more nearby genes, providing evidence that for part of the AID loci multiple causal genes exist. While 54 of the AID loci are shared by one or more AID, 17% of them do not share candidate causal genes. In addition to finding novel genes such as ULK3, we also implicate novel disease mechanisms and pathways like autophagy in celiac disease pathogenesis. Furthermore, 42 of the AID SNPs specifically affected the expression of 53 non-coding RNA genes. To further understand how the non-coding genome contributes to AID, the SNPs were linked to functional regulatory elements, which suggest a model where AID genes are regulated by network of chromatin looping/non-coding RNAs interactions. The looping model also explains how a causal candidate gene is not necessarily the gene closest to the AID SNP, which was the case in nearly 50% of cases. Highlights: Functional genomics implicated 233 causal genes from 120 loci associated to 14 autoimmune diseases. 53 causal disease genes are noncoding RNAs and suggest a role in chromatin looping. 54 loci were shared between diseases but for 9 of these the causal genes differed. Autophagy was also implicated as a molecular mechanism in diseases other than IBD.